Spacing Manipulation: An Approach of Fodder and Food Production from Maize - Premy, K.P.; Devkota, N.R. (Journal of the Institute of Agriculture and Animal Science, 2004)
An alternate approach of fodder as well as grain production was studied by utilizing space between standard rows of maize. Rows of maize plants were added in such space in order to harvest them as a fodder during growth period of maize at different days after sowing, viz. 45, 60 and 75 days after sowing (DAS). The experiment was conducted in a split plot design with four replicates. The main plots were maize varieties and the sub plots were cutting of added rows of maize in different days after sowing (DAS). The four maize varieties used were Ganesh-1, Rampur Composite, Narayani and Upahar. The standard rows to rows spacing were 25x75 cm. The extra rows were added in the spacing of 37.5x25 cm. The results showed that there was no significant difference for green biomass yield between varieties, while cutting of added rows in different DAS had significant (P<0.01) effect. On the other hand, grain yield was significantly different (P<0.01) for varieties as well as cutting of added rows at different DAS. The results of this study thus showed that additional rows of maize plants could be introduced in between standard rows of maize so that quite a significant quantity of green biomass could be harvested during the period of maize growth. But the effective management of added rows seems important aspect for maximizing the benefit from existing maize growing system. Although the harvest of added rows at 75 DAS could produce maximum green biomass, the grain yield would be less. Likewise, harvesting added rows of maize plants at 45 DAS produced comparatively less total green biomass but reasonable quantity of green biomass was possible to collect without much affecting the grain yield. Among the maize varieties studied, Rampur Composite proved to be the best in terms of green fodder and grain yield. J. Inst. Agric. Anim. Sci. 25:47-53 2004